Financial Resilience and Financial Education among Malaysi-an Women Small and Micro Business-Owners: Lessons beyond the Covid-19 Crisis - Mahadi, Nur Farhah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
Abstract Policy makers across the countries have embraced financial education as a remedy to barrier militating against the need of women small and micro business owners to improve their financial decisions, behaviours, and invariably financial resilience and economic opportunities. A review of academic and policy literature on financial education and financial inclusions shows that policymakers have initiated different activities with focus on building and improving financial literacy of groups of women entrepreneurs who operates small and micro businesses. In order to highlight this important objective, one that resonates with development objectives, the paper discusses the following: first, the benefits of financial education for low-income group, in particular, women who operates micro and small businesses; Second, how financial education can support financial inclusions; and third, how financial education could be applied to deal with risks and challenges confronting the low income groups of women business owners, and enhance their financial resilience through appropriate financial decision making and adaptation over a long term. This paper finds relevance in the light of numerous financial challenges such as, financial shortfall, loss of income, trouble meeting other financial obligations experienced by group of low-income groups of women business owners during the COVID-19 pandemic crisis. One that has proven to be a severe test on their financial resilience. This research is supported by Ministry of Education (MOE) through Fundamental Research Grant Scheme (FRGS/1/2021/SS01/UIAM/03/3).